Best International Marketing Track Paper Award in the Academy of Marketing Conference, Hull, U.K. for “Emotional intelligence as a facilitator of long-term orientation in exporter-importer relationships” (with L. Leonidou, B. Aykol, T. Fotiadis) - Christodoulides, Paul (My University, 2026)
International Marketing Track Paper Award
Keywords: Sciences